The Role of Goldschmidt's Tolerance Factor in the Formation of A2BX6 Double Halide Perovskites and its Optimal Range. Issue 5 (30th July 2019) - Fedorovskiy, Alexander E.; Drigo, Nikita A.; Nazeeruddin, Mohammad Khaja
Abstract: Vacancy‐ordered double perovskites is a new branch of lead‐free halide perovskites with properties promising for photovoltaic application. In this study, data about the crystal structure of 170 known A2 BX6 ( X = I, Br, Cl, F) are collected and analyzed to solve a question of applicability of the Goldschmidt's tolerance factor and octahedral factor to double perovskites. It is found that Goldschmidt's tolerance factor is applicable for double perovskites in analog with ABX3 perovskites. Suggested optimal ranges of Goldschmidt's factor expand the geometrical approach from ABX3 perovskites to A2 BX6 double perovskites. The result is useful for up to 796 new full inorganic compounds having double‐perovskite structure and designing new hybrid organic–inorganic double perovskites. Abstract : Existing experimental data about A2 BX6 systems are observed to explore the applicability of Goldschmidt's tolerance factor for vacancy‐ordered double halide perovskites. Halide‐dependent optimal areas and its clearness trends are noted. Furthermore, potential existence of 796 full inorganic double perovskites is predicted.